An overview performance of particle swarm optimization for Economic Dispatch - Aminuddin, Nordin (2022)
Economic Dispatch is one of fundamental in power system studies and becomes an important part of the operation and planning for utilities. As Economic Dispatch very complex in nature, therefore metaheuristic optimization approach has been used to solve it. Multiple approaches were developed to meet the best optimization in Economic Dispatch. Particle Swarm Optimization PSO is one of the most widely used to optimize the system to due flexibility and efficiency. Therefore, need to further study performance PSO to be implemented in Economic Dispatch for balancing supply and load demand. The objective of this study to compare multiple set of generators for dispatching to determine fuel cost whereby optimization can be achieved using the PSO technique. This project proposed MATLAB Software for simulation work. In the end, the results would help to determine the best approach using PSO thus allowing optimization on the system.